The Incorporation of Etanercept into a Porous Tri-Layer Scaffold for Restoring and Repairing Cartilage Tissue - Yaima Campos; Gastón Fuentes; Amisel Almirall; Ivo Que; Timo Schomann; Chih Kit Chung; Carla Jorquera-Cordero; Luis Quintanilla; José C. Rodríguez-Cabello; Alan Chan; Luis J. Cruz (MDPI AG, 2022)
Cartilage diseases currently affect a high percentage of the world's population. Almost all of these diseases, such as osteoarthritis (OA), cause inflammation of this soft tissue. However, this could be controlled with biomaterials that act as an anti-inflammatory delivery system, capable of dosing these drugs over time in a specific area. The objective of this study was to incorporate etanercept (ETA) into porous three-layer scaffolds to decrease the inflammatory process in this soft tissue. ETA is a blocker of pro-inflammatory cytokines, such as tumour necrosis factor alpha (TNF-α) and interleukin 6 (IL-6). For this reason, the scaffold was built based on natural polymers, including chitosan and type I collagen. The scaffold was grafted next to subchondral bone using hydroxyapatite as filler. One of the biomaterials obtained was also crosslinked to compare its mechanical properties with the non-treated one. Both samples' physicochemical properties were studied with SEM, micro-CT and photoacoustic imaging, and their rheological properties were also compared. The cell viability and proliferation of the human chondrocyte C28/I2 cell line were studied in vitro. An in vitro and in vivo controlled release study was evaluated in both specimens. The ETA anti-inflammatory effect was also studied by in vitro TNF-α and IL-6 production. The crosslinked and non-treated scaffolds had rheological properties suitable for this application. They were non-cytotoxic and favoured the in vitro growth of chondrocytes. The in vitro and in vivo ETA release showed desirable results for a drug delivery system. The TNF-α and IL-6 production assay showed that this drug was effective as an anti-inflammatory agent. In an in vivo OA mice model, safranin-O and fast green staining was carried out. The OA cartilage tissue improved when the scaffold with ETA was grafted in the damaged area. These results demonstrate that this type of biomaterial has high potential for clinical applications in tissue engineering and as a controlled drug delivery system in OA articular cartilage.